Pengaruh radiasi plasma pijar korona terhadap viabilitas, laju perkecambahan, dan morfologi kecambah biji bayam cabut (Amaranthus tricolor L.) - Ulfi Nadzifah; Erma Prihastanti (Jurnal Biologi Tropika, 2019)
Corona glow discharge plasma is a source of ions, electrons and free radicals. Free air contains a lot of gas that cannot be absorbed directly by plants. Plasma radiation is able to ionize gas from the air into an ionic form that is fired in a material including seeds. This study aims to determine the effect of time variation of plasma radiation on viability, germination rate and morphology of spinach seeds (Amaranthus tricolorL.). The study was conducted at the CPR Laboratory (Center Plasma Research), Diponegoro University through the RAL method. The observations carried out included viability, germination rate, and morphology of spinach plant sprouts unplug after plasma radiation was carried out on seeds by control treatment, radiation 10 minutes and 20 minutes. The results obtained were analyzed using the ANOVA test and the follow-up test with a significance level of 0.05. Radiation treatment for 20 minutes, 10 minutes and controls gave 100% average viability results; 96.6%; and 53.3%, germination rate of 3.46 n / day; 3.33 n / day; and 3 n / day, the average epicotile length is 0.4 cm; 1.46 cm; and 1.43 cm, the average radicular length is 0.46 cm; 0.36 cm; and 0.14 cm, and the average length of the plumula 0.2 cm; 0.16 cm; and 0.13 cm. Plasma radiation for 20 minutes gives optimal results compared to other treatments, based on the DMRT test showing significant differences between variations in irradiation.